2019
DOI: 10.1038/s41598-018-38243-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new High Resolution Melting (HRM) assay for identification and differentiation of Mycobacterium tuberculosis complex samples

Abstract: The rapid identification and differentiation of members of the Mycobacterium tuberculosis complex (MTBC) is essential to assess the potential zoonotic risk. Different available molecular methods are time consuming since they depend on cultivation of mycobacteria. High Resolution Melting (HRM) is a low cost, rapid and easy to perform single-tube method not limited to cultured samples. In this study, a HRM assay specifically targeting gyrB was developed to simultaneously identify and differentiate Mycobacterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Some recent microbiological applications that used this technology have been reported. Various studies in Switzerland (Landolt et al ), USA (Esteves et al ), Italy (Pugliese et al ), and China (Lu et al ) demonstrated the potential of HRM to differentiate between bacterial species rapidly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent microbiological applications that used this technology have been reported. Various studies in Switzerland (Landolt et al ), USA (Esteves et al ), Italy (Pugliese et al ), and China (Lu et al ) demonstrated the potential of HRM to differentiate between bacterial species rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…Human sources of errors cannot be excluded (Tong and Giffard 2012). In some studies, it has been emphasized how primer and magnesium concentration, as well as annealing temperature, affects the Tm specificity and overall efficiency of the Real-time HRM assay (Esteves et al 2018;Landolt et al 2019).…”
Section: Analytical Sensitivity and Specificity Of Primersmentioning
confidence: 99%
“…4 School of Paramedical, Hamadan University of Medical Sciences, Hamadan, Iran. 5 Nutritious Research Center, School of Medicine, Hamadan University of Medical Sciences, Hamadan, Iran.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The accuracy and efficiency are the advantages of this method. The major challenge to develop this method is applying the most specific melt temperature for each target [5].…”
Section: Introductionmentioning
confidence: 99%
“…HRM is used to characterize samples according to their dissociation behavior as they transition from dsDNA to ssDNA with increasing temperature and uorescence detection. HRM melt curves is a function of the amplicon DNA sequence, which allows discrimination of amplicons with different nucleotide sequence based on melt curve shape, regardless of the amplicon Tm [8,9]. The melt curve analysis is generally used in conjunction with HRM.…”
Section: Introductionmentioning
confidence: 99%